Compression tests on cold formed steel lipped C-Channel columns - short column - Ting, T. C. H.; Lau, Hieng Ho; Law, Ming Chiat (Federation of Engineering Institutions of Islamic Countries, 2010)
This paper presents the test results and structural behaviour of cold-formed steel short c-channel columns with varying thickness and validates the finite element model. The lipped channel sections were tested in fixed-fixed and pinned-fixed ends condition to determine the compressive strength of the sections. The test results are compared with the theoretical results calculated using the Effective Width Method (EWM) and the Direct Strength Method (DSM). A finite element model is also developed using LUSAS v14.3 and the finite element result was compared with theoretical and experimental results. The experiments show that the failures of short columns are generally local and distortional buckling. From test observation, local buckling occurred before distortional buckling, and the ultimate load is usually achieved shortly after distortional buckling occurs. The results obtained from the finite element model generally agree well with the experimental results.